A practical guide to interpreting and generating bottom‐up proteomics data visualizations. Issue 8 (15th February 2022) - Schessner, Julia Patricia; Voytik, Eugenia; Bludau, Isabell
Abstract: Mass‐spectrometry based bottom‐up proteomics is the main method to analyze proteomes comprehensively and the rapid evolution of instrumentation and data analysis has made the technology widely available. Data visualization is an integral part of the analysis process and it is crucial for the communication of results. This is a major challenge due to the immense complexity of MS data. In this review, we provide an overview of commonly used visualizations, starting with raw data of traditional and novel MS technologies, then basic peptide and protein level analyses, and finally visualization of highly complex datasets and networks. We specifically provide guidance on how to critically interpret and discuss the multitude of different proteomics data visualizations. Furthermore, we highlight Python‐based libraries and other open science tools that can be applied for independent and transparent generation of customized visualizations. To further encourage programmatic data visualization, we provide the Python code used to generate all data figures in this review on GitHub (https://github.com/MannLabs/ProteomicsVisualization ).